Metal Nanoclusters with Synergistically Engineered Optical and Buffering Activity of Intracellular Reactive Oxygen Species by Compositional and Supramolecular Design - B. Santiago-Gonzalez (Nature Portfolio, 2017)
Abstract Metal nanoclusters featuring tunable luminescence and high biocompatibility are receiving attention as fluorescent markers for cellular imaging. The recently discovered ability of gold clusters to scavenge cytotoxic reactive oxygen species (ROS) from the intracellular environment extends their applicability to biomedical theranostics and provides a novel platform for realizing multifunctional luminescent probes with engineered anti-cytotoxic activity for applications in bio-diagnostics and conceivably cellular therapy. This goal could be achieved by using clusters of strongly reactive metals such as silver, provided that strategies are found to enhance their luminescence while simultaneously enabling direct interaction between the metal atoms and the chemical surroundings. In this work, we demonstrate a synergic approach for realizing multifunctional metal clusters combining enhanced luminescence with strong and lasting ROS scavenging activity, based on the fabrication and in situ protection of Ag nanoclusters with a supramolecular mantle of thiolated-Au atoms (Ag/Au-t). Confocal imaging and viability measurements highlight the biocompatibility of Ag/Au-t and their suitability as fluorescent bio-markers. ROS concentration tests reveal the remarkable scavenging activity of Ag-based clusters. Proliferation tests of cells in artificially stressed culture conditions point out their prolonged anti-cytotoxic effect with respect to gold systems, ensuring positive cell proliferation rates even for long incubation time.